Acquiescence response styles: A multilevel model explaining individual-level and country-level differences. (1st March 2017) - Rammstedt, Beatrice; Danner, Daniel; Bosnjak, Michael
Abstract: Acquiescence has been found to distort the psychometric quality of questionnaire data. Previous research has identified various determinants of acquiescence at both the individual and the country level. We aimed to synthesize the scattered body of knowledge by concurrently testing a multilevel model encompassing a set of presumed predictors of acquiescence. Based on a representative sample comprising almost 40, 000 respondents from 20 European countries, we analyzed the effects of the country-level indicators economic wealth, corruption level, and collectivism and the individual-level indicators age, gender, educational attainment, and conservatism. Results revealed that 15% of the variance in acquiescence was due to country-level variations in corruption levels and collectivism. Differences among individuals within countries could be partially explained by conservatism and educational attainment. Highlights: Representative sample of almost 40, 000 respondents from 20 European countries Concurrent testing in a multilevel model presumed predictors of acquiescence Country-level indicators corruption rate and degree of collectivism most predictive Differences of individuals in countries due to conservatism and education